Effects of applying mobility localization on source routing algorithms for mobile ad hoc network - Rajan, H. (Proceedings of the Eighth IEEE Symposium on Computers and Communications. ISCC 2003, 2003)
Network topology in mobile ad hoc networks is subject to constant/abrupt change. Source routing algorithms tend not to perform well due to this unstable topology, which invalidates the source routes often, however, the changes in the topology are often local due to the continuous nature of physical movement of nodes. The hypothesis behind this work is that performance of source routing algorithm can be enhanced by localizing these changes in the source route due to mobility, called "mobility localization". Rest of the work discusses and evaluates this hypothesis.